2019
DOI: 10.3390/su11226279
|View full text |Cite
|
Sign up to set email alerts
|

Food Purchasing Decisions and Environmental Ideology: An Exploratory Survey of UK Shoppers

Abstract: Environmentally and ethically conscious food purchasing has traction with British consumers. We examined how broad environmental worldviews related to shoppers’ ratings of the importance of various shopping criteria, including recognition of eco-labels, by surveying 502 shoppers from the city of Sheffield, England. Environmental worldviews were measured using the New Ecological Paradigm (NEP) scale. Responses to the scale split into two dimensions reflecting the scale’s origins: the Dominant Social Paradigm (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 56 publications
0
5
1
1
Order By: Relevance
“…Considering the preferences of consumers, which is the largest sample considered in the survey, our findings of the higher importance of social and ethical issues and animal welfare issues in comparison to health and safety and food quality issues is contrary to the findings of a study in the analysis of the importance of different food shopping criteria in Sheffield, England [62]. The authors found that attributes related to food quality and safety were valued higher than animal welfare and fair trade (ethical issue).…”
Section: Discussioncontrasting
confidence: 99%
“…Considering the preferences of consumers, which is the largest sample considered in the survey, our findings of the higher importance of social and ethical issues and animal welfare issues in comparison to health and safety and food quality issues is contrary to the findings of a study in the analysis of the importance of different food shopping criteria in Sheffield, England [62]. The authors found that attributes related to food quality and safety were valued higher than animal welfare and fair trade (ethical issue).…”
Section: Discussioncontrasting
confidence: 99%
“…The mediating role of EI will be further discussed later in the section. Whilst some studies report the differences in which anthropocentric and biospheric values are associated with GPPI, they also claim that green marketing strategies can be better or only implemented in a market segment that largely shares anthropocentric values (Barker et al, 2019; DellaSala, 2020; ÖZdemİR, 2020). Therefore, the present study informs green marketing strategists to focus more on EI to enhance GPPI amongst individuals with anthropocentric values.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has examined both altruism and anthropocentrism in studies measuring attitudes towards the environment [ 48 ], consumer pro-environmental and ethical purchase intentions [ 50 ] and FAW [ 51 ]. Hence, understanding the role that altruism and anti-anthropocentrism play is important to assessing the drivers of CH meat choices amidst growing competition with plant-based meat or protein alternatives.…”
Section: Literature Reviewmentioning
confidence: 99%